ANALISIS PENDAPATAN USAHATANI PADI SAWAH DI KECAMATAN BIBOKI MOENLEU KABUPATEN TIMOR TENGAH UTARA PROVINSI NUSA TENGGARA - Agripina Ambone; Yosefina M. Fallo; Umbu Joka (Revenue : Jurnal Ekonomi Pembangunan dan Ekonomi Islam, 2020)
This study aims to determine 1) an overview of lowland rice farming 2) income of lowland rice farming in Biboki Moenleu District. This research was conducted from January 2019 to completion. Determination of the sample using simple random sampling technique, namely randomly amounting to 100 respondent farmers. The types of data used are primary data and secondary data. The data analysis method used is descriptive qualitative method and income analysis. The results of the study: 1) The description of lowland rice farming in Biboki Moenleu District includes land processing, seed preparation, planting, maintenance, harvest and post-harvest. ; 2) The total variable cost incurred is Rp. 211,820,066, -; The total depreciation expense incurred is Rp. 32,700,654, and the total income is Rp. 870,269,280, and the R / C ratio value of 4.5.